Effect of the microbial additive VITAFERT on the intake of dry matter and neutral detergent fiber in Saanen goats fed Brachiaria brizantha hay - Guti?rrez, Delf?n; El?as, Arabel; Garc?a, R.; Herrera, F.; Jord?n, Humberto; Sarduy, Luc?a (Cuban Journal of Agricultural Science, 2012)
A microbial additive, VITAFERT (a product biologically active, rich in yeasts and lactobacilli and their metabolites) was included in a basic ration of Brachiaria brizantha hay of low nutritive quality to assess its effect on the voluntary intake of dry matter (DM) and neutral detergent fiber (NDF) in goats from the Saanen breed. In a Latin square design and for 45 d, three Saanen goats of three years of age were used, with average live weight of 43 kg (17.0?0.82 kg LW0.75), out of lactation and canulated in the rumen. The treatments were: T1) basic diet of B. brizantha hay + caprine commercial supplement; T2 and T3) B. brizantha hay + caprine commercial supplement and two levels VITAFERT (6.0 and 12.0 ml kg LW-1). Different from the hay that was offered twice (08:30 and 16:30 h) at a rate of 1.2 kg animal-1 (DB), the levels were added to the supplement at the supply time (09:30 h) according to the treatments. The intake of DM, NDF and their expressions were higher (P < 0.001) in the level of 6.0 ml kg LW-1 of VITAFERT in the ration, with great ratio NDF-TN-1 and higher use of nutrients (ME vs. CP P < 0.001) in the ration, compared to the rest of the treatments. It is concluded that the addition of this microbial additive at a rate of 6.0 ml kg LW-1, in a basic diet of Brachiaria brizantha hay of low quality, together with a minimum of energy-protein supplement, had an associative effect between both of them, increasing the intake of DM and NDF. Key words: Sannen, rumen, associative.